Bettering communication around advance care planning including DNACPR discussions and use of the Urgent Care Plan for patients admitted under Care of Older People - Rena Kaur; Maryam Noeman; Imran Mannan (Future Healthcare Journal, 2024)
Introduction: Advance care planning (ACP) offers patients and their families the opportunity to plan ‘their future wishes and priorities for care’.1 Urgent care plans (UCPs) are intended for patients with a shorter life expectancy and centre around ceilings of care, understanding disease progression, CPR decisions and patients’ preferences.2 These conversations encourage patient empowerment and promote holistic care.3 UCPs can be edited and accessed by healthcare professionals in hospitals and the community to guide care and ensure patients’ wishes are met.2 Our department identified a need to improve the quality and frequency of these conversations. Our aim was to assess current practice, understand barriers, improve communication around ACP and the use of UCPs for patients admitted to elderly medicine. Materials and methods: Data was collected from patients with frailty admitted to the elderly medicine ward over a 6-week period (n=40). This included information on demographics, clinical frailty scale, treatment escalation plan (TEP) and DNACPR discussions, documentation, and use of UCPs. Following data collection, a focus group took place with the medical team to identify any barriers to ACP. Educational interventions were implemented, including a teaching session delivered by the specialist palliative care team. Survey data was collected pre- and post-teaching to assess impact. Results and discussion: Baseline data collection identified that 75% patients had TEP discussions, with 78% patients having a DNACPR order placed appropriately. One quarter of patients had a UCP on admission but only two were reviewed, and no UCPs were initiated during that admission.Focus group data showed time was the biggest barrier to having ACP discussions due to competing clinical demands of staff. Junior doctors expressed a lack of confidence in having these important conversations and felt that these needed to be senior led. Doctors also reported practical difficulties accessing and editing UCPs.Initial survey data showed medical team confidence in DNACPR discussions, with 100% responding confident to very confident, but only 33% were confident using UCPs in practice. Following intervention, doctors’ confidence in using UCPs increased from 33% to 82% and the percentage of doctors reviewing UCPs a few times a week or more, increased from 0% to 55%. Conclusion: Overall, pre-intervention doctors felt confident having DNACPR discussions but less confident in using UCPs in daily practice and consequently, rarely accessed them. Post-intervention data showed significant improvements in use and confidence, highlighting the power of education in raising awareness of ACP.Time constraints and lack of experience were identified as barriers for doctors accessing UCPs. There is also a need to create a more efficient and accessible UCP form. Future steps will include teaching to the wider MDT, equipping all staff members with the tools and confidence to have these important conversations with patients and their relatives. Further interventions also include introducing an ACP prompt to the clerking proforma and discharge summary, ensuring continuity of care between the hospital and community.